High-toughness scratch-resistant PMMA (polymethyl methacrylate) multilayer composite material and preparation method thereof
By using alternate layered PMMA and PMMA/ABS layers in PMMA materials, combined with the toughening modification and multi-layer multiplication technology of ABS high-glue powder, the brittleness problem of PMMA materials under impact and water absorption is solved, and the performance improvement of high strength, toughness, scratch resistance is achieved, and it is suitable for a variety of high-end industrial applications.
Patent Information
- Application Number
- CN202411620508.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-13
AI Technical Summary
PMMA materials are prone to rupture under the action of high impact energy, and due to the presence of ester groups, they are prone to absorb water and cause room temperature creep, which in turn causes stress cracking. At the same time, their surface hardness is insufficient and they are easily scratched by hard objects.
The PMMA layer and PMMA/ABS layer are arranged alternately in layered shapes. The PMMA/ABS layer contains 85-95 parts of PMMA resin, 5-15 parts of ABS high glue powder, 1-5 parts of wear-resistant agent, 2-6 parts of compatibilizer, 1.5-3 parts of antioxidants and 0.5-1 part of additives. It is prepared by a micro-nano multilayer composite preparation system. The PMMA is toughened by ABS high glue powder, and the dispersion and tensile orientation of ABS high glue powder during the multi-layer multiplication process is formed to form a synergistic mechanism of efficient energy dissipation.
It realizes the high strength, tough scratch resistance of PMMA materials, enhances the impact and friction resistance of the materials, and maintains the characteristics of low-cost continuous production, and is suitable for automotive parts and electronic product packaging and other fields.
Smart Images

Figure CN119704815A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-toughness and scratch-resistant PMMA multilayer composite material and a preparation method thereof, belonging to the technical field of high-performance multilayer composite materials. Background Art
[0002] Polymethyl methacrylate (PMMA) has excellent transparency, electrical insulation, and excellent light resistance, weather resistance and anti-aging properties. Therefore, the application range of PMMA composite materials is becoming more and more extensive. It is widely used in the automotive field and the field of electronic product packaging and is constantly expanding to the high-end industrial chain. However, PMMA has a certain brittleness and will break under the action of high impact energy. At the same time, the presence of ester groups makes PMMA easy to absorb water and has obvious room temperature creep, which will cause stress cracking during molding and use. In addition, the surface hardness of PMMA is insufficient and it is easily scratched by hard objects; the scratch resistance of PMMA materials is usually improved by increasing the surface hardness of the material or reducing the surface friction coefficient of the material. Generally, the surface hardness of the material is improved by adding a resin or filler with a higher hardness than the existing material, but this method will cause the toughness of the material to decrease, resulting in mechanical properties that cannot meet the requirements. Summary of the invention
[0003] The object of the present invention is to provide a high-toughness and scratch-resistant PMMA multilayer composite material and a preparation method thereof to solve the above-mentioned problems.
[0004] The technical solution adopted by the present invention is as follows:
[0005] A high-strength, tough, and scratch-resistant PMMA multilayer composite material, the multilayer composite material comprising PMMA layers and PMMA / ABS layers arranged in alternating layers, the PMMA / ABS layers comprising the following raw materials in parts by weight: 85-95 parts of PMMA resin, 5-15 parts of ABS high-rubber powder, 1-5 parts of wear-resistant agent, 2-6 parts of compatibilizer, 1.5-3 parts of antioxidant, and 0.5-1 part of auxiliary agent.
[0006] The wear-resistant agent is ultra-high molecular weight polyethylene powder or zirconium hydrogen phosphate cross-linked silicon dioxide particles, and the particle size range is 5-200 μm.
[0007] The method for preparing the zirconium hydrogen phosphate cross-linked silicon dioxide particles comprises the following steps:
[0008] Step 1, adding zirconium hydroxide to a phosphoric acid aqueous solution to react and obtain a zirconium hydrogen phosphate suspension;
[0009] Step 2, mixing silica sol, water and ammonia water to obtain a silica sol mixed solution, and then adding ethanol;
[0010] Step 3, adding an organic solvent containing fluorine-containing silane to the mixed solution obtained in step 2 to carry out a grafting reaction;
[0011] Step 4, adding the zirconium hydrogen phosphate suspension to the mixed solution obtained in step 3, filtering the product after the reaction, and vacuum drying to obtain zirconium hydrogen phosphate cross-linked silicon dioxide particles.
[0012] In step 1, the concentration of the phosphoric acid aqueous solution is 40-60wt%, the reaction conditions are 80-110°C for 1-5h, and the molar ratio of zirconium hydroxide to phosphoric acid is 2-6:1.
[0013] In step 2, the weight ratio of silica sol, water and ammonia water is 1:3-6:3-6, the solid content of silica sol is 10-30%, the concentration of ammonia water is 5-15wt%; the volume ratio of silica sol mixed solution and ethanol is 1:5-15.
[0014] In step 3, the fluorine-containing silane is 1H,1H,2H,2H-perfluorodecyltrichlorosilane, the concentration is 0.5-5wt%, and the organic solvent is a hydrocarbon solvent or an ester solvent; the volume ratio of the organic solvent containing the fluorine-containing silane to ethanol is 1:0.5-1.5; and the grafting reaction conditions are 30-60°C for 1-10h.
[0015] In step 4, the amount of zirconium hydrogen phosphate suspension added is based on a weight ratio of 1:2-5 between Zr(OH)2 in the converted raw material and SiO2 converted from silica sol, and the reaction conditions are 10-40°C for 10-30h.
[0016] The thickness ratio of the PMMA layer to the PMMA / ABS layer is 1:0.5-1.5.
[0017] The total number of layers of the modified PMMA layer and the PMMA / ABS layer is 32-512 layers.
[0018] The butadiene segment content in the ABS high-rubber powder is greater than 60%.
[0019] The antioxidant is a hindered phenol antioxidant 1010 and a complex phosphite antioxidant 168 in a weight ratio of 1:1-3.
[0020] The method for preparing the above-mentioned high-toughness and scratch-resistant PMMA multilayer composite material comprises the following steps:
[0021] (1) Drying PMMA resin and ABS high-rubber powder separately;
[0022] (2) premixing PMMA resin, ABS high rubber powder, wear-resistant agent, compatibilizer, antioxidant and auxiliary agent according to weight ratio, and then melt-extruding and granulating to obtain PMMA / ABS blend;
[0023] (3) The dried PMMA and PMMA / ABS blends are respectively added to the feeders of extruder A and extruder B of the micro-nano multilayer composite preparation system, merged through a merger, and then sequentially extruded through a layer multiplier, a parallel extrusion die, and pulled by a pulling device to obtain a PMMA multilayer composite material.
[0024] In step (2), the processing temperature of each zone of melt extrusion is 210-240° C., and the speed of the feeding screw is 25-30 rpm / min.
[0025] In step (3), the feeding frequency of extruder A and extruder B is 30-60HZ; the processing temperature of single screw extruder A and extruder B is 220-275°C.
[0026] In step (3), the processing temperature of the combiner and the layer multiplier is 270-275°C, and the die temperature is 265-275°C.
[0027] Beneficial Effects
[0028] The beneficial effects of the present invention are:
[0029] 1. The present invention adopts a micro-nano multilayer composite preparation system to prepare PMMA composite materials, and uses ABS high-rubber powder with a high rubber phase to toughen and modify PMMA, and performs in-situ multi-stage stretching on the polymer melt to stretch and orient the ABS high-rubber powder dispersed phase in the PMMA matrix. At the same time, in the micro-nano multilayer multiplication process, the ABS high-rubber powder toughening phase in the PMMA matrix causes phase deformation due to the dual mechanism of compression stress and tensile stress, thereby forming a scale-refined ABS high-rubber powder toughening phase; the micro-nano layered interface toughening of PMMA and the blending toughening modification of the high elastic rubber system are organically combined to achieve efficient toughening of PMMA resin materials.
[0030] 2. ABS high-rubber powder contains a high content of butadiene segments with a high rubber phase (PB rubber particles). By blending PMMA with it, a PMMA composite material with a balance of high rigidity and high toughness can be obtained. At the same time, core-shell structure copolymers, block copolymers or random copolymers are used as compatibilizers to effectively adjust the compatibility of PMMA / ABS high-rubber powder.
[0031] 3. The ultrafine ultra-high molecular weight polyethylene powder used in the present invention is used as a wear-resistant agent. The ultra-high molecular weight polyethylene powder with a highly physically entangled structure is processed into extremely fine particles, and through the design of a micro-nano stacked structure, it can be evenly and effectively dispersed in the PMMA system, giving the PMMA composite material very excellent impact resistance and friction resistance. The silica particles with fluorine grafted on the surface and cross-linked with zirconium hydrogen phosphate are used as wear-resistant agents in the present invention. After the fluorine modification of the silica surface, the problem of poor dispersion of inorganic silica wear-resistant particles in the polymer is solved, and zirconium hydrogen phosphate is used to combine with silica nanoparticles through covalent bonds to improve the wear resistance of the particles.
[0032] 4. By adjusting the processing conditions to control the morphology of the aggregated phase, a PMMA-based nano-multilayer composite structure is constructed. By inducing the forced phase deformation and multi-level heterogeneous interface of the dispersed phases such as toughening agents and wear resistant agents in the multi-layer confined space, a synergistic mechanism of efficient energy dissipation is constructed to achieve a high rigidity-toughness dynamic balance, and a low-cost, continuously producible, high-strength, tough, and scratch-resistant PMMA multilayer composite material is prepared for use in automotive parts and electronic product packaging, and its application in high-end industries is broadened. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a schematic diagram of the microstructure of high-strength, tough and scratch-resistant PMMA multi-layer composite materials during the micro-nano multi-layer co-extrusion preparation process.
[0034] Figure 2 is a photograph of a multilayer composite material of the present invention. DETAILED DESCRIPTION
[0035] Example 1
[0036] A high-strength, tough, and scratch-resistant PMMA multilayer composite material comprises PMMA layers and PMMA / ABS layers which are arranged in alternating layers, wherein the layer thickness ratio of the two layers is 1:1 and the total number of layers is 512.
[0037] Among them, the PMMA / ABS layer is prepared by raw materials including 95 parts of PMMA resin, 5 parts of ABS high-rubber powder, 5 parts of wear-resistant agent, 4 parts of compatibilizer, 1.5 parts of antioxidant, and 0.5 parts of auxiliary agent by weight, wherein the wear-resistant agent is ultra-high molecular weight polyethylene powder with a mesh size of 10-30μm.
[0038] The method for preparing the high-toughness and scratch-resistant PMMA multilayer composite material comprises the following steps:
[0039] (1) After PMMA resin and ABS high-rubber powder are dried and dehumidified separately, PMMA resin, ABS high-rubber powder, wear-resistant agent, compatibilizer, antioxidant and auxiliary agent are premixed according to the above weight ratio and melt-extruded to granulate. The processing temperature of each zone of melt extrusion is 210-240° C., and the feeding screw speed is 25-30 rpm / min to obtain PMMA / ABS blend.
[0040] (2) The dried PMMA and PMMA / ABS blend are respectively added to the feeders of extruder A and extruder B of the micro-nano multilayer composite preparation system, merged through a merger, and then sequentially extruded through a layer multiplier, a parallel extrusion die, and pulled by a pulling device; the feeding frequency of extruder A and extruder B is 30-60HZ, the processing temperature of single-screw extruder A and extruder B is 220-275°C, the processing temperature of the merger and layer multiplier is 270-275°C, and the die temperature is 265-275°C, to obtain a high-strength, tough, and scratch-resistant PMMA multilayer composite material.
[0041] Example 2
[0042] A high-strength, tough, and scratch-resistant PMMA multilayer composite material comprises PMMA layers and PMMA / ABS layers which are arranged in alternating layers, wherein the layer thickness ratio of the two layers is 1:1 and the total number of layers is 128.
[0043] Among them, the raw materials for preparing the PMMA / ABS layer include 90 parts of PMMA resin, 10 parts of ABS high-rubber powder, 3 parts of wear-resistant agent, 2 parts of compatibilizer, 3 parts of antioxidant and 1 part of auxiliary agent in terms of weight.
[0044] The preparation steps of the high-toughness and scratch-resistant PMMA multilayer composite material are the same as those of Example 1.
[0045] Example 3
[0046] A high-strength, tough, and scratch-resistant PMMA multilayer composite material comprises PMMA layers and PMMA / ABS layers which are arranged in alternating layers, wherein the layer thickness ratio of the two layers is 1:1 and the total number of layers is 32.
[0047] Among them, the PMMA / ABS layer is prepared by raw materials including 85 parts of PMMA resin, 15 parts of ABS high-rubber powder, 1 part of wear-resistant agent, 6 parts of compatibilizer, 3 parts of antioxidant and 1 part of auxiliary agent in parts by weight.
[0048] The preparation steps of the high-toughness and scratch-resistant PMMA multilayer composite material are the same as those of Example 1.
[0049] Example 4
[0050] A high-strength, tough, and scratch-resistant PMMA multilayer composite material comprises PMMA layers and PMMA / ABS layers which are arranged in alternating layers, wherein the layer thickness ratio of the two layers is 1:1 and the total number of layers is 512.
[0051] Among them, the PMMA / ABS layer is prepared by raw materials including 95 parts of PMMA resin, 5 parts of ABS high-rubber powder, 5 parts of wear-resistant agent, 4 parts of compatibilizer, 1.5 parts of antioxidant, and 0.5 parts of auxiliary agent by weight, wherein the wear-resistant agent is fluorine-grafted and zirconium hydrogen phosphate cross-linked silica particles with a mesh size of 10-30μm.
[0052] The preparation method comprises the following steps:
[0053] (1) adding 20 g of zirconium hydroxide to a 50 wt % phosphoric acid aqueous solution at a molar ratio of 4:1 between phosphoric acid and zirconium hydroxide, and reacting at 90-100° C. for 3 h to obtain a zirconium hydrogen phosphate suspension;
[0054] (2) Silica sol, water and ammonia water were mixed in a weight ratio of 1:6:3, wherein the solid content of the silica sol was
[0055] 25wt%, ammonia concentration 5wt%, and the obtained mixture is mixed with ethanol at a volume ratio of 1:8 for 15min, and then a cyclohexane solution of 1H,1H,2H,2H-perfluorodecyltrichlorosilane with a concentration of 1.5wt% is added, and the volume ratio of the cyclohexane solution to ethanol is 1:0.9. After reacting at 40-45°C for 2h, zirconium hydrogen phosphate suspension is added (the added amount is based on the weight ratio of Zr(OH)2 in the converted raw material and SiO2 converted from silica sol of 1:3), and the reaction is carried out at room temperature for 24h. The product is filtered, vacuum dried and ground to obtain fluorine-grafted and zirconium hydrogen phosphate cross-linked silica particles.
[0056] The preparation steps of the high-toughness and scratch-resistant PMMA multilayer composite material are the same as those of Example 1.
[0057] Example 5
[0058] A high-strength, tough, and scratch-resistant PMMA multilayer composite material comprises PMMA layers and PMMA / ABS layers which are arranged in alternating layers, wherein the layer thickness ratio of the two layers is 1:1 and the total number of layers is 512.
[0059] Among them, the PMMA / ABS layer is prepared by raw materials including 95 parts of PMMA resin, 5 parts of ABS high-rubber powder, 5 parts of wear-resistant agent, 4 parts of compatibilizer, 1.5 parts of antioxidant, and 0.5 parts of auxiliary agent by weight, wherein the wear-resistant agent is fluorine-grafted and zirconium hydrogen phosphate cross-linked silica particles with a mesh size of 10-30μm.
[0060] The preparation method comprises the following steps:
[0061] (1) adding 20 g of zirconium hydroxide to a 55 wt % phosphoric acid aqueous solution at a molar ratio of 3:1 between phosphoric acid and zirconium hydroxide, and reacting at 90-100° C. for 2 h to obtain a zirconium hydrogen phosphate suspension;
[0062] (2) Silica sol, water and ammonia water were mixed in a weight ratio of 1:5:4, wherein the solid content of the silica sol was
[0063] 20wt%, ammonia concentration 8wt%, and then the obtained mixture is mixed with ethanol at a volume ratio of 1:9 for 10 minutes, and then a cyclohexane solution of 1H,1H,2H,2H-perfluorodecyltrichlorosilane with a concentration of 2wt% is added, and the volume ratio of the cyclohexane solution to ethanol is 1:0.8. After reacting at 40-45°C for 3h, zirconium hydrogen phosphate suspension is added (the added amount is based on the weight ratio of Zr(OH)2 in the converted raw material and SiO2 converted from silica sol is 1:4), and the reaction is carried out at room temperature for 24h. The product is filtered, vacuum dried and ground to obtain fluorine-grafted and zirconium hydrogen phosphate cross-linked silica particles.
[0064] The preparation steps of the high-toughness and scratch-resistant PMMA multilayer composite material are the same as those of Example 1.
[0065] Example 6
[0066] A high-strength, tough, and scratch-resistant PMMA multilayer composite material comprises PMMA layers and PMMA / ABS layers which are arranged in alternating layers, wherein the layer thickness ratio of the two layers is 1:1 and the total number of layers is 512.
[0067] Among them, the PMMA / ABS layer is prepared by raw materials including 95 parts of PMMA resin, 5 parts of ABS high-rubber powder, 5 parts of wear-resistant agent, 4 parts of compatibilizer, 1.5 parts of antioxidant, and 0.5 parts of auxiliary agent by weight, wherein the wear-resistant agent is fluorine-grafted and zirconium hydrogen phosphate cross-linked silica particles with a mesh size of 10-30μm.
[0068] The preparation method comprises the following steps:
[0069] (1) adding 20 g of zirconium hydroxide to a 50 wt % phosphoric acid aqueous solution at a molar ratio of 5:1 between phosphoric acid and zirconium hydroxide, and reacting at 90-100° C. for 1 h to obtain a zirconium hydrogen phosphate suspension;
[0070] (2) Silica sol, water and ammonia water were mixed in a weight ratio of 1:6:3, wherein the solid content of the silica sol was
[0071] 20wt%, ammonia concentration 10wt%, and the obtained mixture is mixed with ethanol at a volume ratio of 1:7 for 15min, and then a cyclohexane solution of 1H,1H,2H,2H-perfluorodecyltrichlorosilane with a concentration of 2.5wt% is added, and the volume ratio of the cyclohexane solution to ethanol is 1:1. After reacting at 40-45°C for 3h, zirconium hydrogen phosphate suspension is added (the added amount is based on the weight ratio of Zr(OH)2 in the converted raw material and SiO2 converted from silica sol of 1:5), and the reaction is carried out at room temperature for 24h. The product is filtered, vacuum dried and ground to obtain fluorine-grafted and zirconium hydrogen phosphate cross-linked silica particles.
[0072] The preparation steps of the high-toughness and scratch-resistant PMMA multilayer composite material are the same as those of Example 1.
[0073] Comparative Example 1
[0074] Specific implementation method is the same as Example 3, except that no wear-resistant agent is added to the PMMA / ABS layer.
[0075] Comparative Example 2
[0076] The specific implementation is the same as that of Example 3, except that PMMA and PMMA / ABS are two-layer composite materials with a layer thickness ratio of 1:1.
[0077] The method for preparing a PMMA two-layer composite material comprises the following steps: adding dried PMMA to the feeder of a single screw extruder A of a micro-nano multi-layer composite extrusion system, adding dried PMMA / ABS to the feeder of a single screw extruder B of a micro-nano multi-layer composite extrusion system, and extruding flat through a two-layer composite flow channel die; the feeding frequency of the extruder A and the extruder B is 30-60HZ, the melt processing temperature of the single screw extruder A and the single screw extruder B is 220-275°C, and the composite flow channel die temperature is 270°C. Finally, the two-layer composite material of PMMA and PMMA / ABS is obtained by traction through a traction device.
[0078] Comparative Example 3
[0079] Specific implementation method The method is the same as Example 3, except that, in the preparation of silicon dioxide particles, no zirconium hydrogen phosphate suspension is added to perform surface cross-linking of the silicon dioxide particles.
[0080] The PMMA composite materials prepared in Examples 1-6 and Comparative Examples 1-3 were subjected to performance tests, and the performance test standards were as follows: the yield strength test was carried out according to GB / T 1040.2-2006 standard, and the tensile speed was 50 mm / min; the flexural strength test was carried out according to GB / T 9341-2008 standard, and the bending speed was 2 mm / min; the cantilever beam unnotched impact test was carried out according to GB / T 1843-2008 standard; the scratch resistance test was carried out according to GMW 14698 (B method).
[0081] The performance test results are shown in Table 1.
[0082] Table 1 Performance test results of Examples 1-4 and Comparative Examples 1-2
[0083]
[0084] From the comparison of the test results of Examples 1-6 and Comparative Examples 1-3, it can be seen that the present invention uses a highly elastic rubber body to toughen and a wear-resistant agent, and the two synergistically toughen, and utilizes the melt shear characteristics under multi-layer restricted scales to promote the toughening and wear-resistant agent to form a smaller-scale nano-dispersed phase, and utilizes the multi-layer heterogeneous interface for energy absorption and consumption, maintains the rigidity of the PMMA matrix at a relatively low rubber elastomer content and achieves efficient toughening and wear resistance, and prepares a high-strength, tough, and scratch-resistant PMMA multilayer composite material. At the same time, it can be seen from the comparison of Example 1 and Comparative Example 1 that the ultrafine ultra-high molecular weight polyethylene powder used as the wear-resistant agent is highly physically entangled. The ultra-high molecular weight polyethylene powder of the structure is processed into extremely fine particles, and through the design of the micro-nano stacked structure, it can be evenly and effectively dispersed in the PMMA system, giving the PMMA composite material very superior impact resistance and friction resistance; compared with Example 4 and Comparative Example 3, it can be seen that the present invention uses fluorine-grafted and zirconium hydrogen phosphate cross-linked silica particles as wear-resistant agents. After the fluorine modification of the silica surface, the problem of poor dispersion of inorganic silica wear-resistant particles in the polymer is solved, and zirconium hydrogen phosphate is used to combine with silica nanoparticles through covalent bonds to improve the wear resistance of the particles. A process path and a preparation method are provided for the low-cost continuous preparation of high-rigidity, high-toughness, and scratch-resistant PMMA composite materials, which can meet people's requirements for high rigidity, high-toughness, and scratch resistance of materials, and realize the application of low-cost, lightweight shell and component materials.
Claims
1. A high-toughness and scratch-resistant PMMA multilayer composite material, characterized in that: The multilayer composite material comprises PMMA layers and PMMA / ABS layers arranged in alternating layers, wherein the PMMA / ABS layers comprise the following raw materials in parts by weight: 85-95 parts of PMMA resin, 5-15 parts of ABS high-rubber powder, 1-5 parts of wear-resistant agent, 2-6 parts of compatibilizer, 1.5-3 parts of antioxidant and 0.5-1 part of auxiliary agent.
2. The high-toughness and scratch-resistant PMMA multilayer composite material according to claim 1, characterized in that: The wear-resistant agent is ultra-high molecular weight polyethylene powder or zirconium hydrogen phosphate cross-linked silicon dioxide particles, and the particle size range is 5-200 μm.
3. The high-toughness and scratch-resistant PMMA multilayer composite material according to claim 2, characterized in that: The method for preparing the zirconium hydrogen phosphate cross-linked silicon dioxide particles comprises the following steps: Step 1, adding zirconium hydroxide to a phosphoric acid aqueous solution to react and obtain a zirconium hydrogen phosphate suspension; Step 2, mixing silica sol, water and ammonia water to obtain a silica sol mixed solution, and then adding ethanol; Step 3, adding an organic solvent containing fluorine-containing silane to the mixed solution obtained in step 2 to carry out a grafting reaction; Step 4, adding the zirconium hydrogen phosphate suspension to the mixed solution obtained in step 3, filtering the product after the reaction, and vacuum drying to obtain zirconium hydrogen phosphate cross-linked silicon dioxide particles.
4. The high-toughness and scratch-resistant PMMA multilayer composite material according to claim 3, characterized in that: In step 1, the concentration of the phosphoric acid aqueous solution is 40-60wt%, the reaction conditions are 80-110°C for 1-5h, and the molar ratio of zirconium hydroxide to phosphoric acid is 2-6:1; in step 2, the weight ratio of silica sol, water and ammonia water is 1:3-6:3-6, the solid content of silica sol is 10-30%, and the concentration of ammonia water is 5-15wt%; the volume ratio of the silica sol mixed solution to ethanol is 1:5-15.
5. The high-toughness and scratch-resistant PMMA multilayer composite material according to claim 3, characterized in that: In step 3, the fluorine-containing silane is 1H,1H,2H,2H-perfluorodecyltrichlorosilane, the concentration is 0.5-5wt%, and the organic solvent is a hydrocarbon solvent or an ester solvent; the volume ratio of the organic solvent containing the fluorine-containing silane to ethanol is 1:0.5-1.5; the grafting reaction conditions are 30-60°C for 1-10h; In step 4, the amount of zirconium hydrogen phosphate suspension added is based on a weight ratio of 1:2-5 between Zr(OH)2 in the converted raw material and SiO2 converted from silica sol, and the reaction conditions are 10-40°C for 10-30h.
6. The high-toughness and scratch-resistant PMMA multilayer composite material according to claim 1, characterized in that: The thickness ratio of the PMMA layer to the PMMA / ABS layer is 1:0.5-1.5; the total number of layers of the modified PMMA layer and the PMMA / ABS layer is 32-512 layers.
7. The high-toughness and scratch-resistant PMMA multilayer composite material according to claim 1, characterized in that: The ABS high-rubber powder has a butadiene segment content greater than 60%; the antioxidant is a hindered phenol antioxidant 1010 and a complex phosphite antioxidant 168 in a weight ratio of 1:1-3.
8. The method for preparing the high-toughness and scratch-resistant PMMA multilayer composite material according to claim 1, characterized in that: The steps include: (1) Drying PMMA resin and ABS high-rubber powder separately; (2) premixing PMMA resin, ABS high rubber powder, wear-resistant agent, compatibilizer, antioxidant and auxiliary agent according to weight ratio, and then melt-extruding and granulating to obtain PMMA / ABS blend; (3) The dried PMMA and PMMA / ABS blends are respectively added to the feeders of extruder A and extruder B of the micro-nano multilayer composite preparation system, merged through a merger, and then sequentially extruded through a layer multiplier, a parallel extrusion die, and pulled by a pulling device to obtain a PMMA multilayer composite material.
9. The method for preparing the high-toughness and scratch-resistant PMMA multilayer composite material according to claim 8, characterized in that: In step (2), the processing temperature of each zone of melt extrusion is 210-240° C., and the speed of the feeding screw is 25-30 rpm / min.
10. The method for preparing the high-toughness and scratch-resistant PMMA multilayer composite material according to claim 8, characterized in that: In step (3), the feeding frequency of extruder A and extruder B is 30-60HZ; the processing temperature of single screw extruder A and extruder B is 220-275°C; in step (3), the processing temperature of the combiner and layer multiplier is 270-275°C, and the die temperature is 265-275°C.
Citation Information
Patent Citations
Self-lubricating stain-resistant friction-resistant plastic
CN111320835A
Alternating layered PMMA-based composite sheet and preparation method thereof
CN117754944A
Composite decorative plate and production process thereof
CN117944343A
Sheet composite for a bathtub
KR1019990047186A